2022
DOI: 10.3389/fimmu.2022.887380
|View full text |Cite
|
Sign up to set email alerts
|

Cancer Associated Fibroblasts - An Impediment to Effective Anti-Cancer T Cell Immunity

Abstract: The presence of functionally efficient cytotoxic T lymphocytes (CTL) in the Tumour nest is crucial in mediating a successful immune response to cancer. The detection and elimination of cancer cells by CTL can be impaired by cancer-mediated immune evasion. In recent years, it has become increasingly clear that not only neoplastic cells themselves, but also cells of the tumour microenvironment (TME) exert immunosuppressive functions and thereby play an integral part in the immune escape of cancer. The most abund… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 93 publications
(178 reference statements)
0
12
0
Order By: Relevance
“…There is increasing interest in the role of stromal cells in tumour immunity. 3639 Our data illustrates CD39 and CD73 expression on stromal cells with characteristic shape of fibroblasts and which are in close proximity to T cells. We have previously described bidirectional upregulation of CD39 and CD73 elicited by CAF – T cell crosstalk.…”
Section: Discussionmentioning
confidence: 66%
“…There is increasing interest in the role of stromal cells in tumour immunity. 3639 Our data illustrates CD39 and CD73 expression on stromal cells with characteristic shape of fibroblasts and which are in close proximity to T cells. We have previously described bidirectional upregulation of CD39 and CD73 elicited by CAF – T cell crosstalk.…”
Section: Discussionmentioning
confidence: 66%
“…Though the CAF secretome is still not fully characterized, there is evidence that CAF-secreted cytokines and growth factors may trigger the immunosuppressive functions that involve various immune cells and stages of anti-tumoral activity [ 50 , 51 ]. Recent studies have highlighted the direct implication of CAFs in the tumor immunosuppressive microenvironment by excluding T-cells from tumors [ 52 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that lymphocytes have a key role in anti-cancer immunity ( 31 ). Circulating monocytes in the cancer microenvironment differentiate into macrophages ( 32 ).…”
Section: Discussionmentioning
confidence: 99%